Cultural equity: knowledge and outcomes aspects. Issue 1 (14th February 2020) - Torelli, Carlos J.; Oh, Hyewon; Stoner, Jennifer L.
Abstract : Purpose: The purpose of this paper is to propose cultural equity as a construct to better understand the characteristics that define a culturally symbolic brand and the downstream consequences for consumer behavior and nation branding in the era of globalization. Design/methodology/approach: This paper is an empirical investigation of the knowledge and outcome aspects of cultural equity with a total of 1, 771 consumers located in three different countries/continents, 77 different brands as stimuli, and using a variety of measures, surveys, lab experiments, procedures and consumer contexts. Findings: Cultural equity is the facet of brand equity attributed to the brand's cultural symbolism or the favorable responses by consumers to the cultural symbolism of a brand. A brand has cultural equity if it has a distinctive cultural symbolism in consumers' minds (brand knowledge aspect of cultural equity: association with the central concept that defines the culture, embodiment of culturally relevant values and embeddedness in a cultural knowledge network), and such symbolism elicits a favorable consumer response to the marketing of the brand (outcome aspect of cultural equity: favorable evaluations and strong self-brand connections). Practical implications: This paper offers a framework that allows marketers to develop cultural positioning strategies in hyper-competitive and globalized markets and identify ways for building and protecting their brands' cultural equity. Originality/value: This paper advances our understanding of brands as cultural symbols by introducing cultural equity and integrates prior research on brand equity, cross-cultural differences in consumer behavior, country-of-origin effects and nation branding.